STUDI TENTANG ANTECEDENT BRAND ATTITUDE DAN BRAND EQUITY (Penelitian Empirik Iklan TV Provider GSM Prabayar Mentari versi â€œObral Obrolâ€ di Semarang) - Naafiani, Chellya Niken Hayyu (Master of Management Diponegoro University, 2010)
This study examines the process of brand attitude and brand image in enhancing brand equity.This research was done because of the research gaps from previous research on brand attitude proposed in the study Aaker (1991) and Keller (1993) that marks a positive attitude will help improve equity. This is supported by the Cobb-Walgren, Ruble and Donthu (1995) in Faircloth et al. (2001) states that the brand attitude and brand image of a positive influence on brand equity, however, it conflicts with a study conducted by Sitinjak and J. R. S. (2005) which states that the indirect influence brand attitude on brand equity through brand image.From the above problems underlying this research is to find out how to improve brand equity byendorser attractiveness, effectiveness of advertising messages, levels of communicative language,brand attitude, brand image. In this study developed a theoretical model to propose six hypotheses to be tested using Structural Equation Model (SEM) using AMOS software. Respondents in this study were students and people who have worked, at least 18 years of age, minimal education highschool degree, who was lived in Semarang and witnessed or known GSM prepaid card ad in this case is GSM Mentari prepaid card ad â€œObral Obrolâ€ edition which amounted to 120 respondents.Results from SEM data processing for the full model modification indices have largely meet the criteria of goodness of fit as follows chi square = 255.099; probability = 0.158; CMIN/DF =1.091, GFI = 0.854, TLI = 0.990, CFI = 0.991, RMSEA = 0.028. Thus it can be said that this model is feasible to use. The results of this study demonstrate the process to enhance brand equity by improving endorser attractiveness, effectiveness of advertising messages, levels of communicative language, brand attitude, brand image.